ANALISIS PENINGKATAN KUALITAS PELAYANAN MAHASISWA MAGISTER MANAJEMEN TEKNOLOGI ITS SURABAYA DENGAN METODE SERVQUAL DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Noer, Lissa Rosdiana (Universitas Nahdlatul Ulama Sidoarjo, 2016)
MMT-ITS Study Program is a program that has orientations in developing and implementing Technology Management science. This program has some fields and they are Industrial Management, Project Management, and Information Technology Management. Service quality can be known by using Service Quality Methods, they are: (i) tangible, (ii) reliability, (iii) responsiveness, (iv) assurance, and (v) emphaty. The assesment of service levels use questionnaire and this research propose to use Gap 5. Based on the integration result of Servqual Method and Importance Performance Analysis (IPA), MMT-ITS students’ satisfaction will be reached by improving some variables, they are: motorcycle parking space, availability of cleaning service, the ease of delivering facilities and infrastructures complaints, the efficiency of security guard (a main priority of quadrant I). Maintaining the achievement of quadrant II includes: quick in delivering academic information, satisfying literatures of books/references/journals, good lecture materials comprehension, online journal can be accessed easily and fast, any replacement class, fast response to students’ complaints, the ease of academic students’ complaints, the good conditions of tables and chairs, clean classroom, employees willing to give lectures information, clarity in giving information related to college payment and another activities, guarantee of students’ data confidentiality, bright light in the room, safe feeling in students, polite and kind employees, room temperature which is cool. While, another very important variables are fast wifi/internet facility and clean toilet (quadrant IV that has high satisfaction level).